Establishing Polycistronic Expression in the Model Microorganism Ustilago maydis - Müntjes, Kira; Philipp, Magnus; Hüsemann, Lisa; Heucken, Nicole; Weidtkamp-Peters, Stefanie; Schipper, Kerstin; Zurbriggen, Matias D.; Feldbrügge, Michael (Frontiers in Microbiology, 2020)
Eukaryotic microorganisms use monocistronic mRNAs to encode proteins. For synthetic biological approaches like metabolic engineering, precise co-expression of several proteins in space and time is advantageous. A straightforward approach is the application of viral 2A peptides to design synthetic polycistronic mRNAs in eukaryotes. During translation of these peptides the ribosome stalls, the peptide chain is released and the ribosome resumes translation. Thus, two independent polypeptide chains can be encoded from a single mRNA when a 2A peptide sequence is placed inbetween the two open reading frames. Here, we establish such a system in the well-studied model microorganism Ustilago maydis. Using two fluorescence reporter proteins, we compared the activity of five viral 2A peptides. Their activity was evaluated in vivo using fluorescence microscopy and validated using fluorescence resonance energy transfer (FRET). Activity ranged from 20 to 100% and the best performing 2A peptide was P2A from porcine teschovirus-1. As proof of principle, we followed regulated gene expression efficiently over time and synthesised a tri-cistronic mRNA encoding biosynthetic enzymes to produce mannosylerythritol lipids (MELs). In essence, we evaluated 2A peptides in vivo and demonstrated the applicability of 2A peptide technology for U. maydis in basic and applied science.